Analysis of Development Needs of Android-Based Dot Cards Media in Mathematics Subject for Children with Medium Intellectual Disability in XI Grade - Asri Dwi Puspasari; Sunardi Sunardi; Subagya Subagya (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2022)
The objective of this research was to obtain the findings of an analysis of students’ and teachers’ needs for Android-based learning media in Mathematics. The focus of this needs assessment was on intellectual disability in IX grade students and teachers at SLB Kota Madiun. The quantitative research method was used, and the research subjects were teachers and students in XI grade with intellectual disability at SLB Kota Madiun. Instrument in this study was a questionnaires. The findings indicated that the analysis of teacher and student needs would use Android-based learning media, particularly in Mathematics subjects, with a percentage of 100%. This showed that teachers and students were strongly agree to create Android-based learning media in Mathematics.